2014
DOI: 10.1016/j.jarmac.2014.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Creating shared reality about ambiguous sexual harassment: The role of stimulus ambiguity in audience-tuning effects on memory.

Abstract: Please cite this article in press as: Pierucci, S., et al. Creating shared reality about ambiguous sexual harassment: The role of stimulus ambiguity in audience-tuning effects on memory. a b s t r a c tBy tuning messages about ambiguous information to their audience's attitude, communicators can reduce uncertainty and form audience-congruent memories. This effect has been conceptualized as the creation of shared reality with the audience. We applied this approach to representations of ambiguous antecedents of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…When the participants were provided with testimonies about a supervisor’s ambiguous behavior toward a female employee, their memory was tuned according to the attitude of the co-witness (the audience). When other information references (such as information of eventual clear-cut harassment) were provided, participants did not tune their memory ( Pierucci et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the participants were provided with testimonies about a supervisor’s ambiguous behavior toward a female employee, their memory was tuned according to the attitude of the co-witness (the audience). When other information references (such as information of eventual clear-cut harassment) were provided, participants did not tune their memory ( Pierucci et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the four necessary conditions that underlie shared reality. Previous studies have demonstrated that the influence of the audience-tuning on communicators' memory is driven by motivation (Echterhoff et al, 2005(Echterhoff et al, , 2009bPierucci et al, 2013Pierucci et al, , 2014. Specifically, shared reality has a certain degree of selectivity, and people are more willing to share reality with the people they like.…”
Section: Introductionmentioning
confidence: 99%
“…Rotundo et al, 2001) suggests that it is quite likely for individuals to have encoded their ambiguous, initial experiences of SH in an ill-formed manner. Furthermore, "audience turning," in which individuals' initial semantic encoding of an event is shaped to align with how they believe a relevant audience's opinion or attitude toward the event will be (Pierucci et al, 2014), provides a theoretical explanation for the reinterpretation of SH memories. Pierucci et al (2014) theorized that an ambiguous understanding of a potentially threatening event, such as SH, creates a need for an epistemic, shared interpretation of it.…”
Section: Theoretical Developmentmentioning
confidence: 99%
“…To combat this issue, organizations are attempting to minimize harassment in the workplace by creating anti-harassment policies (DOL, 201;Dougherty & Goldstein, 2016) and offering harassment training (Levin, 2016). While policies and trainings offer awareness of the functional definitions of workplace harassment, these strategies may prove inadequate for eradicating harassment in the workplace due to ambiguous definitions and confused perceptions of what qualifies as harassment (Branch, Ramsay & Barker, 2013;Gordon, Cohen, Grauer & Rogelbert, 2005;Pierucci, Echterhoff, Marchal, & Klein, 2014;Toker, 2016).…”
Section: Introductionmentioning
confidence: 99%